Public employment - García Celada, Joseba (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
Public employment has an obvious impact on two aspects of vital relevance for any country. On the one hand, it is of significant importance as part of the jobs occupied by the active population and, therefore, it is decisive in the employment levels of the labour market as a whole, and on the other hand, the quality of the human resources of the Public Administrations is directly associated with the possibility of these to provide the services that they undertake to provide to society and their ability to guarantee the rights of the public administrations. of the citizens. The economic crisis of 2008 had a significant impact on the reduction of staff that has led to an unsustainable situation that has only begun to be arranged in the last four years, although still insufficient for the needs, especially of the General State Administration and specific sectors such as health and education.